Nadzir's Role in the Management of Waqf Mosque Land in Bone Bolango Regency, Indonesia - Pikoli, Yuslan; Rachman, Brilian Rizky; Yasin, Wahid (Talaa : Journal of Islamic Finance, 2021)
The objectives of this research are: to analyze the task of nadzir in land management; to analyze the role of nadzir in the management of land in Bone Bolango Regency; and to describe the factors that affect the role of nadzir in land management. The management of land mosque in Bone Bolango district by Nadzir is clarified by two things, namely effective and ineffective. But the ineffectiveness is dominant, this is because, most nadzir in Bone Bolango district do not really understand what should be their duties, rights and obligations. The research was conducted in Bone Bolango Regency. This type of research is field research. The data sources in this research, are primary and secondary data sources. The data were collected from interviews, observations, and documentation. The results of this research showed that: Nadzir's task in the management of land in Kabupeten Bone Bolango has not been carried out as much as possible by nadzir who should be in charge of managing the land. This is due to their lack of knowledge about the task of nadzir itself.